Steatorrhoea in Acute Enteritis - Sutanto, A. H.; Sa'at, Rahayu; Siregar, H. (Paediatrica Indonesiana, 1982)
Out of a total of 678 patiems, 190 infants presenting acute en1eritis. 95.7% were below 2 yeaÂ·s of age and 86.8% were below 1 year of age. Fat droplets were found in 25 out of 143 patients (17,4%) below 12 months of age. Sugar intolerance was found in 39 of 86 infollts examined (45,3%). The highest prevalence was in the a,;P group of 6- 9 11101:ths. The prevalence of concomitant intestinal parasites was low.